Hyperekplexia, Apneas, Developmental Delay, and Genetic Correlations - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at Swansea University and other centers in the UK, Australia, and Belgium studied the genotype-phenotype correlations in 97 individuals with a clinical diagnosis of hyperekplexia; 61 cases had mutations in GLRA1, 24 cases in SLC6A5 and 12 in GLRB.